Enzymatic Potential of Rhizobacteria from the Amazon - Cassiane Minelli-Oliveira; Paulo Rocha de Oliveira Jr; André Luis Willerding; Luiz Antonio de Oliveira (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Currently, about 6000 enzymes are known, but the amount is much higher than this number, especially if we consider regions of high biological diversity as in the Amazon rainforest. In plant rhizosphere, the chances of finding pathogenic bacteria in humans are very low, providing a safe genetic resource to be exploited biotechnologically. Research has indicated some products and enzymes of economic interest present in rhizobacteria isolated from Amazonian environments, such as plant growth hormones, phosphate solubilization, amylases, proteases, lipases, which could serve as raw material for the installation of bioindustries in the region. Most of our studies with the Amazonian microbiota aim to evaluate its functional genes, of economic and ecological interest. Enzymes such as cellulases, hemicellulases, ligninases, phosphatases, nitrogenases, lipases, chitinases, pectinases are of agronomic and forestry interest, found in regional microorganisms. The Amazonian microbiota has a high diversity and high biotechnological potential. This high microbial potential needs to be better known so that it can effectively contribute to regional and national development through the world market for enzymes and other metabolites of economic interest.